Variations in growth and toxicity in Gymnodinium catenatum Graham from the Gulf of California under different ratios of nitrogen and phosphorus - J J Bustillos-Guzmán; C J Band-Schmidt; D J López-Cortés; I Gárate-Lizárraga; EJ Núñez-Vázquez; FE Hernández-Sandoval (Ciencias Marinas, 2011)
A strain of Gymnodinium catenatum Graham (GCCV-7), isolated from the Gulf of California, was submitted to conditions with different nitrogen-to-phosphorus ratios (5.4, 9.2, 23.5, 44.7, and 74.3) to determine the effect of these ratios on the growth, toxicity, and variations in toxin profile. No differences in toxicity and toxin profile were found among the treatments. Highest cell density occurred at the N:P ratio of 23.5:1, yielding 33% more cells than the 44.5:1 and 74.3:1 treatments, which in turn had 34% and 30% more cells than the 5.4:1 and 9.2:1 treatments. Toxin cell quota and variations in toxin composition were clearly related to growth rates. Toxicity remained relatively invariable because of changes in toxin composition rather than changes in the toxin cell quota during the different growth stages. The data suggest that changes in the N:P ratios do not stimulate production of toxins or changes in toxin profiles, but do affect cell density, and that cellular toxin dynamics is related to the growth stage.